2015
DOI: 10.1039/c4ay02434f
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of fatty compounds from fingerprints for GCMS analysis

Abstract: The composition of fingerprints can contain a wealth of information with regard to the donor of the fingerprint. Fatty acids and other related sebaceous materials can be used to classify donor groups, as previously reported. The extraction of these particular materials from the fingerprint entities has proven to be rather tedious and difficult to reproduce on standardised samples. We present a two step method to obtain a broad spectrum of sebaceous materials from fingerprints in high yields with good reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
(24 reference statements)
2
17
0
Order By: Relevance
“…Both endogenous (i.e., triacylglycerols (TGs), fatty acids (FAs), amino acids, and peptides) and exogenous compounds (drugs, explosives, bug sprays, sunscreens, food related, etc.) detected in latent fingerprints have been utilized to develop suspect profiles and differentiate individuals (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Matrix-assisted Laser Desorption/ionizationmentioning
confidence: 99%
“…Both endogenous (i.e., triacylglycerols (TGs), fatty acids (FAs), amino acids, and peptides) and exogenous compounds (drugs, explosives, bug sprays, sunscreens, food related, etc.) detected in latent fingerprints have been utilized to develop suspect profiles and differentiate individuals (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Matrix-assisted Laser Desorption/ionizationmentioning
confidence: 99%
“…Intrinsic components detected in latent fingerprints have already been identified through numerous forensic studies as an important index for the development of fingerprints (Gird et al 2012;Bailey et al 2016;Ramotowski et al 2001;Rohatgi and Kapoor 2016;Bohanan 1998;Asano et al 2002;Croxton et al 2010;Stewart et al 1989;Antoine et al 2010;Michalski et al 2013a;Archer et al 2005;Cadd et al 2015a;Cadd et al 2015b). These studies showed that the components of a fingerprint are 95-99% water and organic (protein, amino acids, urea, and lipids) and inorganic (sodium, potassium, chloride, and phosphate) compounds secreted from eccrine, apocrine, and sebaceous glands.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds originate from the sebum secreted by the sebaceous glands and are very useful ingredients to visualize fingerprints (Rohatgi and Kapoor 2016). Fatty acids are used as a particular target ingredient, which is important for aging studies due to its oxidation over time and the fact that it can be used to identify donor gender, age, eating habits, and race (Bohanan 1998;Asano et al 2002;Croxton et al 2010;Stewart et al 1989;Antoine et al 2010;Michalski et al 2013a;Archer et al 2005;Cadd et al 2015a). A better understanding of the composition changes over time is required to improve detection and visualization of the latent fingerprint and can also be useful in providing clues to criminal investigations (Cadd et al 2015b;Girod et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 By extracting the fatty components from ngerprints using CHCl 3 , Girod et al succeeded in obtaining full proles of a substantial amount of ngerprints. Even though it appeared later that the extraction methods used may not have been the optimum conditions, 7,8 Girod et al have shown the great potential of chemical proling of ngerprints on the basis of exogenous and endogenous materials. And even though the fatty acids, squalene, cholesterol and triglycerides found in ngerprints may not be directly related to the nger or palm deposition, more information on what has been touched previous to the crime related deposition can be invaluable.…”
Section: Introductionmentioning
confidence: 99%